Social Class and Gender in an Equation of Students’ Mathematics Identity - Mićić, Katarina; Jovanović, Olja (Studies in Teaching and Education, 2025)
Addressing the achievement gap in mathematics across social class and gender is essential, as mathematics is widely seen as a pathway to social mobility and a tool for breaking cycles of inequality. Using a Bourdieusian perspective and the concept of mathematical identity, this study investigates the hindering and supporting processes in disadvantaged students’ identification with mathematics. Six disadvantaged fourth and fifth graders were interviewed to explore and describe their mathematical identities. The findings reveal that students from disadvantaged backgrounds face systemic challenges in school mathematics as soon as they encounter school mathematics, resulting in low confidence and negative self-perceptions. These students recognize the societal importance of mathematics, while they feel personally and academically disconnected from it, creating tensions in their relationship with the subject. The students don’t follow the institutional requirements for mathematics success, as they are focused on fulfilling short-term academic goals. Boys appear to have a slight advantage, as aspects of their mathematical identities can be reinforced by their gender identities, though this comes with additional pressures and responsibility. In contrast, girls from disadvantaged families lack any foundation for basing their mathematical identity on. Improving mathematics education for disadvantaged students requires teachers to recognize and address systemic barriers, including implicit taken-for-granted rules, biases and implicit messages, while creating opportunities for all students to feel competent and find mathematics meaningful. However, true equity demands systemic change, starting with curriculum developers and teacher education programs, to dismantle traditional barriers and redesign mathematics as an inclusive and accessible domain for all.